Clinical spectrum and genetic variation of six patients with methylmalonic aciduria (MMA); a report from Iran - Zahra Beyzaei; Hossein Moravej; Mohammad Hadi Imanieh; Sorour Inaloo; Bita Geramizadeh (BMC Pediatrics)
Abstract Objective Methylmalonic acidemia (MMAs) is known as a severe, complex, and lethal disorder of methylmalonate and cobalamin. The patients with MMA may have developmental, neurological, and metabolic disorders such as liver disease. Here, we aim to evaluate 6 Iranian patients suspected to MMA disorder. Study design We will provide genetic results, biochemical analysis and treatment for these patients. Liquid chromatography-tandem mass spectrometry (LC–MS/MS) and variant screening in probands by whole exome sequencing (WES) were performed. Results A total of six homozygous variants were identified, including five previously identified variants and one novel variant, in the two MMA-causing genes as follows: c.577G > C, c.290 + 69G > T, c.662T > A, c.290 + 69G > T of MMAB, and c.100dupA, c.394 C > T of MMACHC. Sanger sequencing confirmed the identified variants. Additionally, metabolomics data analysis reliably identified elevated C3 and MMA levels, as well as abnormalities in the amino acid profile, indicating the presence of pathogenic variants. Conclusions Our findings expand the global spectrum of genotypes in MMA. While WES, combined with metabolomics and biochemical analysis, offers valuable insights for accurate diagnosis and subtyping of MMA, it is most beneficial in complex cases where clinical findings are unclear.